Bending Speed Dependence Properties of Stiffness of Anisotropic Viscoelastic Fin Containing Fiber Composite Dilatant Fluid (Journal of Fiber Bioengineering and Informatics, 2019)
The stiffness of the elastic fin for underwater propulsion may need to change concerning its bendingspeed. In order to realize the bending speed dependence of stiffness in relation to the structure, we havedeveloped an anisotropic viscoelastic fin containing fiber composite dilatant fluid. For the bending testof the fin to examine its stiffness, the top of the fin is fixed, while the base of the fin is rotated. Thebending resistance force, as the apparent stiffness of the fin, was measured by the load cell connectedto the top of the fin. Bending resistance of the fin containing dilatant fluid increased as the averageangular velocity of bending increased. Furthermore, bending resistance of the fin increased accordingto the existence of fiber, especially the fin along the longitudinal direction of the fiber. This developedfin is a highly functional structure, which can adapt to the demands of changing optimum stiffness withregard to different directions of deformation speed.
Keywords: Bio-inspired Mechanism; Stiffness; Viscoelastic Fin; Dilatant Fluid; Fiber Composite Material